Analisis Margin dan Efisiensi Pemasaran Ikan Bandeng dan Ikan Tongkol di DKI Jakarta (Analysis Marketing Margin and Efficiency of Milkfish and Mackarel Tuna Fish at DKI Jakarta) - D Iwan Riswandi; Wawan Oktariza (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2015)
Ministry of Marine Affairs and Fisheries has continued to roll out policies for the empowerment of fisherman and fish farmers, especially the micro scale. In order to enhance the welfare and income of fish farmers and fisherman, the problems in marketing that need to be getting the attention that is associated marketing margin and efficiency of capture fisheries and aquaculture commodity. The purpose of this study is to analyze marketing margin and efficiency of milkfish and mackarel tuna coming into Jakarta market as well as provide marketing policy recommendations of fishery products. The results showed that the marketing of milkfish and mackarel tuna to the Jakarta market based on marketing costs have been efficient because the costs are relatively low compared to the price of the consumer level. However, based on marketing cost-benefit ratio is not efficient because it can not hold a fair sharing of the overall price paid by the consumers to producers and middleman involved in the production and marketing of the commodity. Therefore, there needs to be marketing regulation to protect the interests of fish farmers, fisherman and consumers in the marketing of fishery commodities.Keyword: marketing efficiency, milkfish and mackarel tuna, marketing regulation